2012
DOI: 10.1189/jlb.0111054
|View full text |Cite
|
Sign up to set email alerts
|

Capture of cell-derived microvesicles (exosomes and apoptotic bodies) by human plasmacytoid dendritic cells

Abstract: cDCs and pDCs differ in multiple aspects. Among those, antigen capture is a recognized feature of cDCs, whereas pDCs display poor capacity to capture cell-derived antigens. However, animal models of organ transplantation suggested a role for pDCs in tolerance induction via phagocytosis of donor antigens. In a transplantation setting, microvesicles, such as apoptotic bodies and exosomes secreted by the graft, may be potential sources of alloantigen. Here, we tested the capacity of human pDCs to capture exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 37 publications
(41 reference statements)
4
28
0
Order By: Relevance
“…So how close are pDCs to cDCs in this capacity? Bastos-Amador et al recently reported that human pDCs have the ability to capture and present exosomes and apoptotic bodies from Jurkat T cells [70]. These observations are consistent with previous reports that identify pDCs as phagocytic antigen-presenting cells essential for tolerance to vascularized cardiac allografts in an animal model of organ transplantation [71].…”
Section: Antigen Presentationsupporting
confidence: 90%
“…So how close are pDCs to cDCs in this capacity? Bastos-Amador et al recently reported that human pDCs have the ability to capture and present exosomes and apoptotic bodies from Jurkat T cells [70]. These observations are consistent with previous reports that identify pDCs as phagocytic antigen-presenting cells essential for tolerance to vascularized cardiac allografts in an animal model of organ transplantation [71].…”
Section: Antigen Presentationsupporting
confidence: 90%
“…It is likely that, in vivo , pDC recognize and engulf apoptotic bodies or exosomes released by MCMV-infected cells, (Figure 2B, ❶), as was demonstrated for other viruses (Dreux et al, 2012) or tumor cells (Bastos-Amador et al, 2012). pDC could also directly recognize and engulf viral particles (Figure 2B, ❷).…”
Section: Molecular Mechanisms Regulating DC Subset Sensing Of and Cymentioning
confidence: 63%
“…They have been shown to lessen the severity of autoimmune mediated arthritis and asthma in mice (48, 49). Human pDCs can also ingest microvesicles from apoptotic cells and present the antigen to T cells (50). In the presence of apoptotic cells, TLR7 activated pDCs greatly augmented T cell expression of IL-10, without affecting T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%